Comparison of Attachment Styles, Resiliency and Social Capital in the Spouses of Martyrs, Veterans and Normal People; A Case Study of Ardabil City - M. Abbasi Abrazgah; SH. Khodaee (Afarand Scholarly Publishing Institute, 2018)
Aims: War is a complex social event that affects institutions and social life. The purpose of this study was to compare the attachment styles, resilience and social capital in the spouses of witness, veterans and normal people. Instruments & Methods: This descriptive cross-sectional study was conducted in 2016 among the spouses of witness, veterans and normal people in Ardabil city. Using cluster sampling, 135 people (45 people in each group) were selected as sample. For data collection, Avdnhavn Attachment Questionnaire, Connor-Davidson Resilience Scale and Social Capital Questionnaire based on the Nahapit and Ghoshal model were used. The data were analyzed by Manova test and LSD test, using SPSS 16 software. Finding: There was no significant difference among three groups in secure attachment (F=0.123; p=0.884) and avoidance attachment (F=0.122; p= 2.136), but there was a significant difference among fearful attachment scores (F=3.164; p=0.045). Also, there was a significant difference among three groups in resilience scores (F=3.770; p=0.026) and social capital scores (F=4.715; p=0.011). Conclusion: The fearful attachment style of veteranschr('39') spouses is more common than normal spouses, but other attachment styles are the same in all three groups. Also, the level of resilience and social capital are different in three groups; So that the resilience of spouses of normal people is higher than veteranschr('39') spouses. The spouses of witness and veterans comparing to normal spouses have higher social capital.